Pengaruh Gaya Mengajar dan Motivasi Belajar terhadap Hasil Belajar Menggiring Bola pada Permainan Sepakbola (Studi Eksperimen di SMPN 2 Manado) - Irvan Kurniawan (Departement of Mathematics Education, 2023)
This study aims to determine the influence of teaching style and motivation on learning the results of dribbling in a soccer game. In addition, this study also aims to determine the effect of motivation on both teaching styles. The teaching style in this study is the opposite of the teaching style in practice, and learning motivation is high and low. Research conducted at SMPN 2 Manado Education Development, Manado City, North Sulawesi, class VIII, 2021–2022. The research method is an experiment with a treatment-level 2x2 design and a sample size of 52 people. The results of this study are as follows: (1) Overall, there is a difference between teaching style and practice teaching style as opposed to dribbling learning outcomes; (2) for students who have high learning motivation, provide an inclusive teaching style to give a better effect than the practice of teaching style on dribbling learning outcomes; (3) for students who have low learning motivation, the provision of practice teaching style gives a better effect than the opposite of inclusive teaching style for dribbling learning outcomes; and (4) there is an interaction between styles of teaching and motivation towards the learning outcomes of dribbling.